2011
DOI: 10.1186/1753-6561-5-s9-s84
|View full text |Cite
|
Sign up to set email alerts
|

A method to detect single-nucleotide polymorphisms accounting for a linkage signal using covariate-based affected relative pair linkage analysis

Abstract: We evaluate an approach to detect single-nucleotide polymorphisms (SNPs) that account for a linkage signal with covariate-based affected relative pair linkage analysis in a conditional-logistic model framework using all 200 replicates of the Genetic Analysis Workshop 17 family data set. We begin by combining the multiple known covariate values into a single variable, a propensity score. We also use each SNP as a covariate, using an additive coding based on the number of minor alleles. We evaluate the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the Discussion section, we present results that were observed by several teams. Song et al [2011] looked for an increase in LOD score (the LodDiff) when a causal SNP was included in the trait model. They found that the LodDiff was highly skewed toward true positives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Discussion section, we present results that were observed by several teams. Song et al [2011] looked for an increase in LOD score (the LodDiff) when a causal SNP was included in the trait model. They found that the LodDiff was highly skewed toward true positives.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al [2011] developed a novel method to analyze affection status. Each affected individual was assigned a propensity score [Doan et al, 2006]; this score is the predicted probability of being affected based on a logistic regression using the significant covariates, calculated in each replicate separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modification of this original two-parameter CL model into a one-parameter model was proposed by Goddard et al ( 2001 ). Linkage analysis using the CL model has been proven to be an effective tool for evaluating genetic linkage (Goddard et al, 2001 ; Arcos-Burgos et al, 2004 ; Reck et al, 2005 ; Doan et al, 2006 ; Rybicki et al, 2007 ; Stein et al, 2007 ; Zandi et al, 2007 ; Song et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%